Research on Primary Frequency Modulation Online Monitoring and Assessment Management System Under “Master–Sub” Control Station Model - Xu, Zhihao; Liu, Chao; Song, Ziyang (Frontiers in Energy Research, 2022)
In modern power system, in order to realize the safe operation of units and maintain the frequency stability of the power network, various means of frequency modulation can be adopted. However, there are some deficiencies in the real-time monitoring and assessment management of Primary Frequency Modulation (PFM). To solve these problems, a PFM on-line monitoring and management method based on “Master – Sub” control station model in Wide Area Measurement System (WAMS) is proposed as a control strategy to support frequency modulation of units and assist power network assessment. In the hybrid monitoring system strategy of the Master control station and Sub control station, the Sub control station is built locally in the power plant to monitor the operational status of the unit in real time and calculate the PFM assessment index. The Master control station is built-in the dispatching center, receiving the assessment data uploaded by the Sub control station and sending the PFM simulation test instruction. This strategy can effectively improve the real-time performance of dynamic monitoring and parameter calculation, and reduce the probability of frame loss and communication instability in long-distance data transmission. The experimental results show that the PFM on-line monitoring management control strategy based on “Master – Sub” control station model can effectively monitor the unit and provide data support for PFM assessment.